2023
DOI: 10.1002/mco2.259
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial‐based gene therapy

Abstract: Gene therapy, a medical approach that involves the correction or replacement of defective and abnormal genes, plays an essential role in the treatment of complex and refractory diseases, such as hereditary diseases, cancer, and rheumatic immune diseases. Nucleic acids alone do not easily enter the target cells due to their easy degradation in vivo and the structure of the target cell membranes. The introduction of genes into biological cells is often dependent on gene delivery vectors, such as adenoviral vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 289 publications
0
13
0
Order By: Relevance
“…A major characteristic of using viral vectors is that they can persist in the body for relatively long periods of time and therefore have the potential to remain highly efficacious. , Regulatory elements, which are DNA sequences that promote or enhance gene expression, can be selected to control and drive high levels of transgene expression . However, current gene therapies lack the ability to be controlled or turned off after administration and could contribute to toxicity if delivered to off-target cells. , Viral vectors are also naturally capable of performing endosomal escape as they evolved to do so in order to infect cells and release their genetic cargo.…”
Section: Designing Biomaterials For In Vivo Cell Programmingmentioning
confidence: 99%
“…A major characteristic of using viral vectors is that they can persist in the body for relatively long periods of time and therefore have the potential to remain highly efficacious. , Regulatory elements, which are DNA sequences that promote or enhance gene expression, can be selected to control and drive high levels of transgene expression . However, current gene therapies lack the ability to be controlled or turned off after administration and could contribute to toxicity if delivered to off-target cells. , Viral vectors are also naturally capable of performing endosomal escape as they evolved to do so in order to infect cells and release their genetic cargo.…”
Section: Designing Biomaterials For In Vivo Cell Programmingmentioning
confidence: 99%
“…The creation of risk-free and efficient gene-editing medicines is being facilitated by developments in biomaterial design, formulation optimization, and safety evaluations. Preclinical research in animal models has shown encouraging findings, suggesting the possibility of clinical use in the future ( Bashor et al, 2022 ; Yu et al, 2023b ).…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…Gene therapy is the introduction of genes into cells to up-regulate the expression of target genes to treat or repair tissue defects [ 2 , 3 ]. It exhibits high specificity, low immune rejection, and durability; it is widely used in the treatment of cystic fibrosis, hereditary retinopathy, multiple sclerosis, bone defect repair, and cancer [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%